Model Implementasi Firewall MikroTik dalam Pengelolaan Trafik dan Keamanan Jaringan - Abraham Cornelius Dachi; Handrie Noprisson (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2025)
This study aims to analyze the role of firewall implementation on MikroTik RouterOS in improving network security and traffic management at CV. Prima Dinamika Mandiri. The company’s network infrastructure consists of an internet service provider router (ISP router), a MikroTik router functioning as the main firewall and gateway, network switches for LAN distribution, multiple access points across work areas, client devices such as laptops, PCs, and servers, as well as shared printers in each office room. The firewall was implemented through several configurations, including filtering rules, brute-force protection, Layer 7 filtering, Network Address Translation (NAT), and Quality of Service (QoS), with the objective of minimizing security threats and optimizing network traffic distribution. The evaluation results demonstrate a significant improvement in network performance, as indicated by the increase in throughput from 90 Mbps to 105 Mbps, the reduction of latency from 20 ms to 15 ms, and the decrease in packet loss from 3% to 0.5%. These findings confirm that the implementation of a MikroTik-based firewall enhances network security, stability, and reliability in supporting the company’s operational activities. Further development opportunities include the integration of Intrusion Detection and Prevention Systems (IDS/IPS) and VLAN segmentation.